Une perspective sur la Transylvanie: Le château des Carpathes de Jules Verne - Martin, Roxana (Études sur la Région Méditerranéenne, 2019)
The region of Transylvania had been for centuries under Ottoman rule. Our study focuses on the novel The Castle of the Carpathians by Jules Verne, published in 1892. The analysis is made of six chapters, leading to the introduction of the origins of the novel, continuing with its main subject followed by the literary theme, the characters, the narrative techniques and, finally, we propose an anthropological point of view of a space found under the Ottoman Empire at a given moment in history. The purpose of our study is to present Jules Verne’s perspective on Transylvania: specific features, detailed descriptions, remarks on its native and foreign inhabitants. Working methods: textual and monographic analysis, anthropological reading.